2016
DOI: 10.1007/s10902-016-9755-8
|View full text |Cite
|
Sign up to set email alerts
|

Interest as a Moderator in the Relationship Between Challenge/Skills Balance and Flow at Work: An Analysis at Within-Individual Level

Abstract: Considering flow as a non-ergodic process (i.e., non-homogeneous across individuals and non-stationary over time) that happens at the within-individual level, in this research we work with Bakker's model that propose flow as made up by three components: intrinsic motivation, enjoyment, and absorption. Taking into account that flow theory can be considered as an intrinsic motivation theory, and the recent proposals about the need to distinguish between pre-conditions of flow and the flow experience itself, we l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…Individuals in demanding situations perceive such situations as challenging but controllable with the help of their skills. Individuals believe that they may succeed to deal with a challenging situation by using their skills ( Bricteux et al, 2016 ). For example, a skilled web designer may experience the flow while working on website illustration because his skills may meet the challenges of the task.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals in demanding situations perceive such situations as challenging but controllable with the help of their skills. Individuals believe that they may succeed to deal with a challenging situation by using their skills ( Bricteux et al, 2016 ). For example, a skilled web designer may experience the flow while working on website illustration because his skills may meet the challenges of the task.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This paper may make significant contributions. First, we examine the role of HIHRM practices (i.e., recognition, empowerment, information sharing, fair rewards, and competence development) in creating a balance between challenges and skills as it is believed to be a basic criterion to trigger the flow ( Csikszentmihalyi, 1990 ; Bakker, 2005 ; Bricteux et al, 2016 ). Second, we propose that HIHRM practices implemented to enhance employee well-being are viewed as important job resources that may positively facilitate the work-related flow and AC.…”
Section: Introductionmentioning
confidence: 99%
“…However, this measurement method may not fully acknowledge the complex nature of the flow phenomenon that may involve both continuous and abrupt changes over time (Ceja and Navarro 2011). Research has indicated that, at the intra-individual level, different dimensions of the work-related flow experience as well as different levels of flow may be associated with different dynamic patterns, non-linear, random, or chaotic Navarro 2011, 2012; see also Bricteux et al 2017). For example, whereas low levels of the challenge-skills balance were associated with a linear pattern, high levels of flow were associated with a non-linear, chaotic pattern.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 99%
“…Challenge demands are positively valued demands, for example complex responsibilities. They allow for growth (Bricteux et al 2017;Ventura et al 2015). Hindrance demands, by contrast, are difficulties that are considered to be potentially harmful for performing one's work (Ventura et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation